Cancer literacy among Jordanian colorectal cancer survivors and informal carers: Qualitative explorations - Melhem, Samar J.; Nabhani-Gebara, Shereen; Kayyali, Reem (Frontiers in Public Health, 2023)
Introduction Cancer patients face a variety of challenges in understanding their diagnosis and treatment options. Making informed decisions requires health literacy. There is scant research on how colorectal cancer (CRC) survivors and their caregivers engage with healthcare systems and obtain cancer-related knowledge to maintain proper health literacy, which is crucial for enhancing their outcomes. Materials and methods In-depth semi-structured interviews (IDIs) with CRC survivors (n = 15) and online focus groups (FG) with informal caregivers (ICs) were held in Amman between Jan-June 2020. In-depth interviews were conducted using semi-structured interview protocol that addressed the healthcare experience of CRC cancer survivors. FGs evaluated ICs' perspectives of e-health for cancer care support. IDIs and FGs were done in the local Jordanian Arabic dialect, which was then translated into English. Transcribed audio-recordings were thematically coded and framework analysis was used. Results The findings are organized around a central concept of “exploring the level of literacy and its impact.” From the overarching theme, three themes and subthemes emerged, including: (1) The current state of counseling and information provision, (2) The impact of lack of information, awareness, and literacy and (3) The health system's influence on literacy. Conclusions Poor cancer literacy hinders patients throughout their cancer journey. Empowering cancer patients is crucial for a more timely and positive patient experience. Increased cancer literacy together with the creation of health-literate organizations and systems have the potential to improve patients' treatment throughout the continuum of care.